Influence​ Culture Organization and Employee Discipline towards Performance Employees at the Department Health Bogor Regency - Leni Laelawati; Rita Rahmawati; Muhammad Husein Maruapey (PT. Lembaga Penerbit Penelitian Nusantara, 2026)
Public health organizations are required to maintain service quality through strong organizational culture and employee discipline. However, empirical studies that specifically examine both variables in local public health institutions remain limited. This study aims to analyze the effect of organizational culture and employee discipline on employee performance at Puskesmas Curug Bitung, Bogor Regency. The study used a quantitative associative approach with a survey design. The population consisted of 32 employees, and 25 respondents were selected as the sample using the Slovin formula. Data were collected through questionnaires, observations, and structured interviews, then analyzed using validity and reliability tests, Pearson Product Moment correlation, coefficient of determination, and partial t-test. The results show that organizational culture has a positive and significant effect on employee performance, with a correlation coefficient of 0.777, R square of 0.630, and t-value of 5.910. Employee discipline also has a positive and significant effect on employee performance, with a correlation coefficient of 0.808, R square of 0.653, and t-value of 6.583. The novelty of this study lies in its direct testing of organizational culture and discipline without mediating variables in a district-level public health service institution. Strengthening service-oriented culture and consistent discipline is therefore essential to improve employee performance.